A study on the enhancement of the tribological properties of nitrile-butadiene rubber reinforced by nano-ZnO particles from an atomic view. (22nd September 2021) - He, Enqiu; Wang, Shijie; Tang, Liming; Chen, Jichi
Abstract: In this study, three-layer molecular models of frictional pair containing nitrile-butadiene rubber matrix reinforced by nano-ZnO particle as the core and Fe layers as the counterparts are first developed. Molecular dynamics simulations are then conducted to explore the enhanced effects of nano-ZnO particle on tribological behaviors of NBR matrix. The simulation results show that the frictional coefficient of NBR matrix can be efficiently reduced of approximately 30% by incorporation of nano-ZnO particle. In order to reveal the atomic inherent mechanisms on the enhanced effects, the radius of gyration, concentration profiles, velocities distributions and temperature profiles of NBR chains are calculated and discussed in detail. Through quantitative validations of experimental works, it can be finally concluded that by incorporation of nano-ZnO particle, due to the strong vdW adsorption forces, NBR chains can be efficiently restricted around the surface of nano-ZnO particle, leading to the whole NBR matrix to perform better ability to avoid adhesive wear phenomenon, better deformation resistance, lower friction coefficients and wear loss, et al In addition, it is also proved that the proposed molecular modeling and dynamics simulation methods can be an efficient way to provide inherent mechanisms for studying tribological properties of nano-ZnO/NBR matrix in addition to experimental works.